c-Src kinase contributes on endothelial cells mechanotransduction in a heat shock protein 70-dependent turnover manner - Pinto, Thaís Silva [UNESP]; Fernandes, Célio Junior da Costa [UNESP]; da Silva, Rodrigo Augusto [UNESP]; Gomes, Anderson Moreira [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Padilha, Pedro de M. [UNESP]; Zambuzzi, Willian F. [UNESP] (Wiley, 2019)
Shear stress changes are associated with a repertory of signaling cascade modulating vascular phenotype. As shear stress-related tensional forces might be associated with pathophysiological susceptibility, a more comprehensive molecular map needs to be addressed. Thus, we subjected human umbilical vein endothelial cells (HUVECs) to a circuit of different tensional forces in vitro considering the following three groups: (a) physiological blood flow shear stress condition (named Normo), (b) a hypertensive blood flow shear stress (named Hyper), and (c) these hyper-stressed cells were returned to Normo condition (named Return). The samples were properly collected to allow different methodologies analysis. Our data showed a pivotal involvement of c-Src on driving the mechanotransduction cascade by modulating signaling related with adhesion, survival (PI3K/Akt) and proliferative phenotype. Moreover, c-Src seems to develop important role during extracellular matrix remodeling. Additionally, proteomic analysis showed strong involvement of heat shock protein 70 (HSP70) in the hypertensive-stressed cells; it being significantly decreased in return phenotype. This result prompted us to investigate 20S proteasome as an intracellular proteolytic alternative route to promote the turnover of those proteins. Surprisingly, our data reveled significant overexpression of sets of proteasome subunit α-type (PSMA) and β-type (PSMB) genes. In conjunction, our data showed c-Src as a pivotal protein to drive mechanotransduction in endothelial cells in a HSP70-dependent turnover scenario. Because shear patterns is associated with pathophysiological changes, such as atherosclerosis and hypertension, these results paved new road to understand the molecular mechanism on driving mechanotransduction in endothelial cells and, if drugable, these targets must be considered within pharmacological treatment optimization.
Keywords: c-Src; endothelial cells; HSP70; hypertension; mechanotransduction; proteasome; shear stress; signaling